Perspectivas teóricas y metodológicas para el estudio del ambiente como determinante de la salud (2016)
ABSTRACT: To describe some of the theoretical and methodological perspectives of the environment as a health determinant, this is a contribution from the conceptual standpoint to this complex field in constant construction and deconstruction. Methodology: the subject was reviewed through an analysis of the literature performed after finding and reading official documents and scientific papers that made it possible to structure the text around the subject. Results and discussion: throughout history, in various discourses and in individual and collective experiences, the environment has been present in the continuum of the health-disease process. Hygiene and sanitation solve the problem in a scenario where there are risks and hazards that should be identified in order to be controlled or removed. However, since the last decades of the twentieth century, the economic interests, along with the global and local environmental damage and the need to preserve health, have caused the environment to be understood, at least theoretically and methodologically, as a determinant of health. This conception in turn implies considering mankind not as the master of nature but as part of it. Conclusions: throughout time it has been observed and experienced that the anthropic interventions of humankind over nature have been disrespectful and have led it to consistently move from the status of victimizer of its surrounding to that of victim of the constructed environments. Environmental health models built with a stronger focus on health should be integrated with other disciplines for the analysis of complex situations in environmental health.